The Role Of Goal Orientation and Social Support Towards Academic Help-Seeking In High School Students With Kurikulum Merdeka - Nugroho, Indra Prapto; Fikri, Muhammad Zainal; Tarigan, Angeline Hosana Zefany; Alfath, Esa Arsyiatul (Jurnal Sains Psikologi, 2024)
This study aims to determine the role of goal orientation and social support towards academic help-seeking in high school students with kurikulum merdeka. The hypothesis of this study is the role of goal orientation and social support on academic help-seeking in high school students. Participants totaled 150 high school students in Indonesia. The sampling technique used was purposive. This study used three scales as measuring instruments, namely the goal orientation scale, social support scale, and academic help-seeking scale. Data analysis in this study was conducted using simple regression analysis techniques. The results showed a significant role between goal orientation and social support variables on academic help-seeking variables with a significance value of 0.000 (p <0.05). The coefficient of determination (R Square) of the three variables is 0.817 which is included in the moderate category. This research can be a basis for educating students that asking for help is normal and beneficial for learning progress by proactively looking for supportive peers or teachers to discuss and help each other in learning.